A first census of skin cancer specialist nurses across UK secondary care trusts - Jashmitha Rammanohar; Deeya Kotecha; Jackie Hodgetts; Saskia Reeken; Susanna Daniels; Pippa G Corrie (BMC, 2023)
Abstract Background Skin cancer specialist nurses (SCSNs) support patients and work alongside healthcare professionals throughout the care pathway. Skin cancer management is rapidly evolving, with increasing and more complex treatment options now available, so the need for patient support is growing. While SCSNs are a major source of that support, the provision of SCSN resource across the UK has never previously been assessed. We therefore undertook a first SCSN census on 1st June 2021. Methods An electronic survey was disseminated to UK hospital trusts and registered skin cancer healthcare professionals. Responses were identifiable only by the respective trust name. Results 112 responses from 87 different secondary care trusts were received; 92% of trusts reporting having at least 1 established SCSN post. Average SCSN staffing per trust was 2.4 (range 0-7) whole time equivalents, managing an average caseload of 83 (range 6-400) patients per week. SCSN workload had increased in 82% hospitals in the previous year and 30% of trusts reported being under-resourced. Most SCSN time was spent managing melanoma (as opposed to non-melanoma skin cancer) patients linked to surgical services. Regional variations existed, particularly associated with provision of lymphoedema services, nurse prescribing skills and patient access to clinical trials. The COVID-19 pandemic was associated with a marked increase in SCSN-led telemedicine clinics, but loss of training and education opportunities. Conclusions SCSNs based in secondary care hospitals play a major role supporting both clinicians and patients throughout the care pathway. This first UK census confirmed that SCSN workload is increasing and in one third of hospital trusts, the work was reported to outstrip the staffing available to manage the volume of work. Regional variations in SCSN resource, workload and job role, as well as availability of certain skin cancer services were identified, providing valuable information to healthcare commissioners concerned with service improvement.